Demographic security of the Krasnodar Region of the Russian Federation as an important factor in ensuring economic security - A. R. Cholakhyan; A. P. Anufrieva (Вестник университета)
Demographic security is an important element of regional and national security, which includes a set of measures aimed at maintaining stable population growth and preserving cultural and ethnic diversity. In the context of economic security, the demographic component plays a key role, as it directly affects region’s labor potential and its investment attractiveness. In the conditions of the demographic crisis, the Krasnodar Region is facing serious economic issues such as labor shortages, declining labor productivity, and rising costs for social services. It may lead to a decrease in its competitiveness in the domestic and foreign markets, as well as to a deterioration in the general standard of living of the population. The issue of demographic security, which is becoming increasingly important, has been studied. The demographic security concept and its main threats have been considered. The number of natural and migratory population growth, affecting the demographic situation in the Krasnodar Region, which creates certain threats to the economic security of the country, has been analyzed. The main issues that require control and attention from the authorities have been outlined.